PENGUMPULAN ZAKAT MELALUI PAYROLL SYSTEM DITINJAU DARI PERSPEKTIF HUKUM ISLAM - Rosyidi, Imron (UIN Fatmawati Sukarno Bengkulu, 2018)
This research is conducted in order to answer the question how the review of Islamic law to the collection of zakat through payroll system? The purpose of this study is to investigate how the review of Islamic law to the collection of zakat through payroll system. This research is library research that is by way of tracing, collecting, clarifying and viewing data from various literatures related to the core problems in order to get the principles and concepts about the problems as the object of research. The approach used in this research is qualitative normative clinical normative Islamic research with fath adz-dzari’ah method. The results of this study show that the collection of zakat through payroll system is valid. Referring to the order of zakat collection to the ruler in Surat At-Taubah verse 103 that to maximize the collection of zakat is something that must be done by the ruler, therefore everything that becomes the means to maximize the collection must also be held, one of them is the method of collecting zakat through payroll system. Therefore the collection of zakat through payroll system according to fath adz-dzari’ah is valid. Collection of zakat through payroll system must intend once every year at the beginning of payment because it is a cicil system.